Técnica de journaling para sistemas de arquivos baseados em memórias não voláteis - Brahm, Lucas (2018)
Emerging non-volatile memories should reach latency as close as volatile memories and shall be connected to the memory bus alongside DRAM. This allows access through read and write instructions in memory in a very fast and simplified way. This new model brings a need to ensure consistency and integrity with high performance. This work proposes to use an optimized file system to work with these memories and to improve its journaling system, one used to ensure consistency and atomicity of metadata. In this work, we use specific processor instructions and reduce write order restrictions, in addition to simplifying the file system management logic. These enhancements have shown performance gains and have maintained the consistency and integrity of file system. The results show that in some specific applications a gain of 49% is possible using one of the proposed solutions.